RANCANGAN MATERI SOSIALISASI BERBASIS PERMENDIKNAS NO 17 TH 2010 BAGI PENCEGAHAN DINI PALGIATOR SKRIPSI MAHASISWA (STUDI RESEARCH AND DEVELOPMENT PADA MAHASISWA FAKULTAS HUKUM UMSU) - Dr Ramlan, S.H, M.Hum (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
Education must stand above the value of truth and honesty. Intellectual measure a student is measured by it's ability to complete the final task, and after that he is worthy of a college degree.